USE OF ICT TO IMPROVE THE QUALITY OF INCLUSIVE EDUCATION (Journal of Information Technologies in Education (ITE), 2013)
The article outlines the main changes in the education system in recent years; reflectes the new educational opportunities for children with disabilities; identifies the possible ways of use of ICT to improve the quality of inclusive education.
Keywords: ICT tools; inclusive education; education of children with special needs; quality of education